The application of Agile Project Management in non-software related projects - Kabata, Apphiah J K (2017)
The business climate has stressed the need for an effective project management approach, resulting in the emergence of the agile approach which involves a constant update to the business environment as to produce what is fit for purpose. It is referred to as a humanistic approach and emphasizes on aspects such as teams and collaboration. The approach has been mostly applied in the IT sector, where it emerged and has, since then, contributed to positive results such as good quality products, and higher customer satisfaction. In the hope of leveraging these benefits, organizations such as Saab, have adopted the concept in a non-software related context. With the aim of establishing a framework that will facilitate the expansion of the concept, this study conducted a theoretical and empirical research to investigate how the concept was used in a non-software context. The findings of this study reveal the presence of new agile elements, each having an influence on the application of the concept. This study proposed a conceptual framework identifying the specific impact of elements, and the sequence in which the elements should be considered. The results of this study can guide practitioners in the application of agile PM by creating an environment that promotes and facilitates the concept.